(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Theoretical works and techniques, different techniques and methods that scientists use in the study of the content and subject matter, presentation of literary and artistic pieces and explore ways of describing in historical works of Mirza Muhammad Haidar Dughlat, indicate the need for a comprehensive analysis of specific literary and historical facts. For in-depth study of "Tarikh-i-Rashidi" requires modern new techniques and technologies. Our achievements so far and the challenges that lie ahead of us will be very useful for future researchers. This is enough to become a strong foundation for future researchers. One can not deny and not take into account the importance of the theoretical conclusions and practical values of these findings. The value of "Tarikh-i-Rashidi" of Mirza Muhammad Haidar Dughlat once told Sh.Valihanov, S.Aspandiyarov, A. Margulan and other research scientists of Kazakh history and literature. Their main works on the study of "Tarikh-i-Rashidi" are well known to the general public. In addition, we must pay tribute to the outstanding scientist-orientalist A.Derbisali for his contribution to "Dulativedenie." We also need to appreciate the works of scientists: S.Kaskabasov, R.Berdibay, N.Kelimbetov, B.Kozhabekuly, T.Omarbekov, B.Komekov, I.Zhemeney and others who have written about the contribution of this work in Turkish literature and history. In "Tarikh-i- Rashidi" we find the presentation, the methods and style inherent in literature, in determining the methods of poetic description and analysis see the words that define the ideas and concepts inherent in the Kazakh national knowledge. Sometimes it is possible to note their accord with medieval terms. It seems, on the specifics of the order we can make their consistent comparison and make solid conclusions.